Iron and steel slag valorization through carbonation and supplementary processes - Georgakopoulos, Evangelos D. (Cranfield University, 2016)
Alkaline industrial wastes are considered potential resources for the mitigation of CO2 emissions by simultaneously capturing and sequestering CO2 through mineralization. Mineralization safely and permanently stores CO2 through its reaction with alkaline earth metals. Apart from natural formations, these elements can also be found in a variety of abundantly available industrial wastes that have high reactivity with CO2, and that are generated close to the emission point-sources. Apparently, it is the applicability and marketability of the carbonated products that define to a great extent the efficiency and viability of the particular process as a point source CO2 mitigation measure. This project investigates the valorization of iron- and steel-making slags through methods incorporating the carbonation of the material, in order to achieve the sequestration of sufficient amounts of CO2 in parallel with the formation of valuable and marketable products. Iron- and steel-manufacturing slags were selected as the most suitable industrial byproducts for the purposes of this research, due to their high production amounts and notable carbonation capacities. The same criteria (production amount and carbonation capacity) were also used for the selection of the iron- and steel-making slag types that are more suitable to the scope of this work. Specifically for the determination of the slag types with the most promising carbonation capacities, the maximum carbonation conversions resulting from recent publications related to the influence of process parameters on the conversion extent of iron- and steel-manufacturing slags, were directly compared to each other using a new index, the Carbonation Weathering Rate, which normalizes the results based on particle size and reaction duration. Among the several iron- and steel-manufacturing slags, basic oxygen furnace (BOF) and blast furnace (BF) slags were found to combine both high production volumes and significant affinity to carbonation. In the context of this research, two different procedures aiming to the formation of value added materials with satisfactory CO2 uptakes were investigated as potential BF and BOF slags valorization methods. In them, carbonation was combined either with granulation and alkali activation (BOF slag), or with hydrothermal conversion (BF slag). Both treatments seemed to be effective and returned encouraging results by managing to store sufficient amounts of CO2 and generating materials with promising qualities. In particular, the performance of the granulation-carbonation of BOF slag as a method leading to the production of secondary aggregates and the sequestration of notable amounts of CO2 in a solid and stable form, was evaluated in this work. For comparison purposes, the material was also subjected to single granulation tests under ambient conditions. In an effort to improve the mechanical properties of the finally synthesized products, apart from water, a mixture of sodium hydroxide and sodium silicate was also tested as a binding agent in both of the employed processes. According to the results, the granules produced after the alkali activation of the material were characterized by remarkably greater particle sizes (from 1 to 5 mm) compared to that of the as received material (0.2 mm), and by enhanced mechanical properties, which in some cases appeared to be adequate for their use as aggregates in construction applications. The maximum CO2 uptake was 40 g CO2/kg of slag and it was achieved after 60 minutes of the combined treatment of alkali activated BOF slag. Regarding the environmental behavior of the synthesized granules, increased levels of Cr and V leaching were noticed from the granules generated by the combination of granulation-carbonation with alkali activation. Nevertheless, the combination of granulation with alkali activation or that of granulation with carbonation were found not to worsen, if not to improve, the leaching behaviour of the granules with regards to the untreated BOF slag. The formation of a zeolitic material with notable heavy metal adsorption capacity, through the hydrothermal conversion of the solid residues resulting from the calcium- extraction stage of the indirect carbonation of BF slag, was also investigated in this project. To this end, calcium was selectively extracted from the slag by leaching, using acetic acid of specific concentration (2 M) as the extraction agent. The residual solids resulting from the filtration of the generated slurry were subsequently subjected to hydrothermal conversion in caustic solution of two different compositions (NaOH of 0.5 M and 2 M). Due to the presence of calcium acetate in the composition of the solid residues, as a result of their inadequate washing, only the hydrothermal conversion attempted using the sodium hydroxide solution of higher concentration (2 M) managed to turn the amorphous slag into a crystalline material, mainly composed by a zeolitic mineral phase (detected by XRD), namely, analcime (NaAlSi2O6·H2O), and tobermorite (Ca5(OH)2Si6O16·4H2O). Finally, the heavy metal adsorption capacity of the particular material was assessed using Ni2+ as the metal for investigation. Three different adsorption models were used for the characterization of the adsorption process, namely Langmuir, Freundlich and Temkin models. Langmuir and Temkin isotherms were found to better describe the process, compared to Freundlich model. Based on the ability of the particular material to adsorb Ni2+ as reported from batch adsorption experiments and ICP-OES analysis, and the maximum monolayer adsorption capacity (Q0 = 11.51 mg/g) as determined by the Langmuir model, the finally synthesized product can potentially be used in wastewater treatment or environmental remediation applications.
Keywords: CO2; Sequestration; BOF steel slag; BF steel slag; carbonation; granulation; alkali activation; aggregates; hydrothermal conversion; zeolites; adsorption